Epidemiology of Huntington disease: first post-HTT gene analysis of prevalence in Italy - Squitieri, F.; Griguoli, A.; Capelli, G.; Porcellini, A.; D'Alessio, B. (Clinical genetics, 2016)
Huntington disease (HD) prevalence shows geographic variability and has been recently updated by taking into account the mutation diagnostic test. In Italy, the last epidemiological estimation was reported well before the HTT gene discovery and the availability of the corresponding genetic test. It reported a prevalence of affected subjects ranging between 2.3 and 4.8/100,000 in some restricted areas of Northern Italy. We have performed a service‐based epidemiological analysis in a very restricted geographic area named Molise, where our institutions currently operate and represent the only point of reference for rare neuropsychiatric diseases. The estimated prevalence rate found was 10.85/100,000 (95% confidence interval (CI): 7.20–14.50), remarkably higher than that previously described before the gene test analysis was available, and expected to an increase of an additional 17% by 2030, because of Italian population aging. According to our analysis, we estimate that about 6500 subjects are currently affected by HD in Italy, and that this number will further increase in the next decades because of population aging, variable phenotype penetrance and improved life expectancy.